Investigation of Social Intelligence Features of Athletes in Different Branches in Terms of Various Variables - Pepe, Şirin (2021)
The population of this study, which was carried out to evaluate the different variables of social intelligence levels of athletes in different branches, included the athletes who participated in group competitions of the sports federations of badminton, basketball, wrestling, hockey, karate, judo, softball, water polo, and table tennis in Turkey, and the sample group consisted of a total of 387 active athletes, 219 females and 168 males with an average age of 15,05 ± 2,06; who participated in competitions and voluntarily accepted to participate in the study. In addition to the demographic form, the Tromso Social Intelligence Scale developed by Silvera et al. (2001) and validity and reliability in Turkish made by Doğan and Çetin (2009) was used to collect data in the study. As a result, while there were no significant differences in the social intelligence levels of the athletes in terms of the gender variable, it was found that they had significant differences according to the sports branch, education level, duration of sportsmanship, and the education level of parents. In this study, it was determined that the athletes got a moderate score from the Tromso Social Intelligence Scale.